1984
DOI: 10.1111/j.1365-2265.1984.tb00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulin in Human Serum: Problems in Measurement and Interpretation

Abstract: The immunoreactivity of an extracted pancreatic human proinsulin standard in an indirect immunoradiometric assay was found to be at least one hundred times higher than that of biosynthetic human proinsulin. Limited tryptic digestion of the biosynthetic proinsulin increased its immunoreactivity in the assay and this was attributed to the production of partially cleaved proinsulin molecules which still retained the C-peptide moeity. This inference was confirmed by the finding that pure samples of 65/A1 and 32/33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Proinsulin levels determined with this antiserum, therefore, represent not only intact proinsulin but also conversion intermediates of proinsulin to an unknown extent. The possibility of cleavage of circulating proinsulin is small [16], but there is evidence that considerable amounts of proinsulin intermediates exist in the blood [17]. Similarly, insulin assay values may include intact proinsulin and its derivatives by crossreaction.…”
Section: Discussionmentioning
confidence: 98%
“…Proinsulin levels determined with this antiserum, therefore, represent not only intact proinsulin but also conversion intermediates of proinsulin to an unknown extent. The possibility of cleavage of circulating proinsulin is small [16], but there is evidence that considerable amounts of proinsulin intermediates exist in the blood [17]. Similarly, insulin assay values may include intact proinsulin and its derivatives by crossreaction.…”
Section: Discussionmentioning
confidence: 98%
“…Identical response curves were obtained whether standards were added in veronal buffer or in serum from which endogenous proinsulin had been removed by prior incubation with immobilized rabbit polyclonal anti-insulin immunoglobulin..Ŝ ubjects. Fasting proinsulin levels and the response to a 75-g glucose load were determined in nine normal, nonobese, healthy subjects (7 men, 2 women) with an age range of 20-24 yr. Levels were determined according to the methods described above (monoclonal assay) and a previously described method (indirect assay) (2,15).…”
Section: Methodsmentioning
confidence: 99%
“…1). We have reported that an indirect two-site immunoradiometric assay that employs polyclonal antisera directed against insulin and C-pepide appears only to measure partially hydrolyzed proinsulins and not intact proinsulin (2). Proinsulin concentrations in human serum measured with this and other methods (4,5) are similar, suggesting that circulating human proinsulin immunoreactivity may be predominantly if not entirely due to hydrolyzed proinsulins.…”
mentioning
confidence: 85%
“…The measurement of proinsulin is complicated by the presence of proinsulin conversion intermediates in the circulation (11,12,36,37). We characterized several cleaved derivatives of proinsulin for cross-reactivity with antibody 168AB (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…First, proinsulin is present in low concentration in serum (8)(9)(10), and proinsulin conversion intermediates are present in fluids and tissues (11,12). Second, other potentially cross-reactive peptides, including insulin and C-peptide, can interfere in some assays.…”
mentioning
confidence: 98%